Distribution and efficacy of ofatumumab and ocrelizumab in humanized CD20 mice following subcutaneous or intravenous administration - Torres, Julia Baguña; Roodselaar, Jay; Sealey, Megan; Ziehn, Marina; Bigaud, Marc; Kneuer, Rainer; Leppert, David; Weckbecker, Gisbert; Cornelissen, Bart; Anthony, Daniel C. (Frontiers in Immunology, 2022)
Approval of B-cell-depleting therapies signifies an important advance in the treatment of multiple sclerosis (MS). However, it is unclear whether the administration route of anti-CD20 monoclonal antibodies (mAbs) alters tissue distribution patterns and subsequent downstream effects. This study aimed to investigate the distribution and efficacy of radiolabeled ofatumumab and ocrelizumab in humanized-CD20 (huCD20) transgenic mice following subcutaneous (SC) and intravenous (IV) administration. For distribution analysis, huCD20 and wildtype mice (n = 5 per group) were imaged by single-photon emission computed tomography (SPECT)/CT 72 h after SC/IV administration of ofatumumab or SC/IV administration of ocrelizumab, radiolabeled with Indium-111 (111In-ofatumumab or 111In-ocrelizumab; 5 µg, 5 MBq). For efficacy analysis, huCD20 mice with focal delayed-type hypersensitivity lesions and associated tertiary lymphoid structures (DTH-TLS) were administered SC/IV ofatumumab or SC/IV ocrelizumab (7.5 mg/kg, n = 10 per group) on Days 63, 70 and 75 post lesion induction. Treatment impact on the number of CD19+ cells in select tissues and the evolution of DTH-TLS lesions in the brain were assessed. Uptake of an 111In-labelled anti-CD19 antibody in cervical and axillary lymph nodes was also assessed before and 18 days after treatment initiation as a measure of B-cell depletion. SPECT/CT image quantification revealed similar tissue distribution, albeit with large differences in blood signal, of 111In-ofatumumab and 111In-ocrelizumab following SC and IV administration; however, an increase in both mAbs was observed in the axillary and inguinal lymph nodes following SC versus IV administration. In the DTH-TLS model of MS, both treatments significantly reduced the 111In-anti-CD19 signal and number of CD19+ cells in select tissues, where no differences between the route of administration or mAb were observed. Both treatments significantly decreased the extent of glial activation, as well as the number of B- and T-cells in the lesion following SC and IV administration, although this was mostly achieved to a greater extent with ofatumumab versus ocrelizumab. These findings suggest that there may be more direct access to the lymph nodes through the lymphatic system with SC versus IV administration. Furthermore, preliminary findings suggest that ofatumumab may be more effective than ocrelizumab at controlling MS-like pathology in the brain.